Phthalate exposure and reproductive effects in rodents: a model for approaches on the protective role of natural products - Scarano, Wellerson Rodrigo [UNESP]; Guerra, Marina Trevizan; Perobelli, Juliana Elaine; Fernandes, Glaura S.A.; Arena, Arielle Cristina [UNESP]; de Aquino, Ariana Musa; Rocha, Vanessa Aguiar [UNESP]; Magosso, Natalia [UNESP]; Souza, Patrick Vieira [UNESP]; Barbisan, Luis Fernando [UNESP] (Oxford University Press (OUP), 2025)
This review article summarizes the experimental findings in rodents published between 2014 and 2024 concerning phthalates exposure and reproductive outcomes. Rodents were chosen for this review because most studies that have focused on developmental aspects in different phases of exposure and that address more in-depth reproductive mechanisms have been carried out in mice and rats. The evidence of adverse effects of phthalates on fetal development and human and animal reproduction is extensive, with impacts ranging from gene expression to physiological alterations. Despite the large volume of scientific papers pointing out the harmful effects of exposure to phthalates, isolated or in mixtures, at different developmental periods, most of them are associated with the maternal exposure and long-term effects in the offspring. Regular vegetables, fruits, fish, dairy products, and whole grains intake rich in bioactive compounds can mitigate the adverse effects of endocrine-disrupting chemicals in humans and animals at different developmental periods. Various food bioactive compounds (FBCs), such as genistein, resveratrol, lycopene, vitamin E, curcumin, selenium, and plant secondary metabolites (PSMs), present antioxidant, anti-inflammatory, antitumor, and other biological properties with the potential to reduce deleterious effects of phthalates on the reproductive tract. In this review, we aimed to summarize the main studies carried out in the last decade about phthalate exposure and reproductive disorders in males and females (at different developmental critical windows). In addition, we proposed some FBCs and PSMs that could attenuate the main adverse effects caused by phthalate exposure on male reproduction because there is a lack of studies with females.
Keywords: food bioactive compounds; natural products; Phthalates; plant secondary metabolites; reproductive tract